KETERPAPARAN DAN SUMBER INFORMASI KESEHATAN REPRODUKSI TERHADAP PERILAKU SEKSUAL REMAJA (SKAP NTB 2019): EXPOSURE AND SOURCES OF REPRODUCTIVE HEALTH INFORMATION ON ADOLESCENT SEXUAL BEHAVIOR (SKAP NTB 2019) - Nurmayani M, Winda; Ilham, Ilham; Mulianingsih, Misroh; Handayani, Baiq (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Adolescence as a transitional period usually has a high curiosity, including those related to sex. Based on Riskesdas 2018, about 1 million teenage boys (5%) and 200,000 girls (1%) openly stated that they had had sex. Adolescent sexual behavior cannot be separated from the negative influence of information technology that can be accessed openly. The purpose of this study was to analyze the relationship between exposure to information and sources of information about reproductive health on sexual behavior of premarital adolescents in NTB. This study uses a Retrospective Correlation design, with a Cross Sectional approach, this study is a secondary data analysis of SKAP 2019. The sample in this study was 982, a total sampling technique. Based on the results of the statistical test analysis of Spearman Rho, a p-value of > 0.05 was obtained. The conclusion of this study is that it is not related to exposure to information and sources of information about reproductive health to premarital sexual behavior in NTB. Recommendations: Further research with qualitative methods is needed to dig deeper into the reasons adolescents engage in premarital sexual behavior.